Management of Ectopic Lens Cataract by Lensectomy, Vitrectomy and Iridial Fixation Implantation (Artisan): About 02 Eyes of a Child Admitted to CHU IOTA - Sidibe, M K; Gnangourou, N.; Tepage, J.; Simaga, A.; Diallo, S.; Conare, I.; Traore, O. Y.; Dembele, F.; Traore, K.; Diarra, M.; et al. (European Journal of Applied Sciences, 2025)
Objective : To report two cases of ectopic cataracts in the context of Marfan's syndrome diagnosed and treated by vitrectomy, lensectomy associated with iridial fixation implantation with good functional results. Case report: This 16-year-old patient was admitted to the African Tropical Ophthalmology University Hospital Center (CHU-IOTA) for a decline in visual acuity since childhood, and was diagnosed as having Marfan syndrome with bilateral ectopic cataract, taking into account the Berlin anatomical criteria. Apart from ocular and musculoskeletal involvement, cardiac, pulmonary, biological and biochemical examinations were normal. After surgical management with vitrectomy, lensectomy and iridofixation implantation (artisan), initial visual acuity counts fingers at 1 meter and at 2 meters in the right and left eyes respectively, improved to 5/10 without correction in both eyes and to 10/10 with optical correction made after postoperative follow-up. Conclusion : Iris-fixation implantation after vitrectomy and lensectomy is an effective surgical technique that can guarantee good functional results in children with ectopic cataracts due to Marfan syndrome.